Liquified hydrogen vs. liquified renewable methane: Evaluating energy consumption and infrastructure for sustainable fuels - Mohammed Al-Breiki (14152476) (2023)
This study aims to assess the energy consumption characteristics of various fuels, namely liquified natural gas, liquefied renewable methane, and liquefied hydrogen from production to overseas transportation, by covering broad color spectra of grey, blue, and green. A quantitative assessment is implemented to calculate how much energy is consumed to produce, store, and transport fuels. Carbon capture scenarios are also considered, along with boil-off gas recovery and utilization options for increased value chain effectiveness. Thereafter, a qualitative assessment is performed to compare the use of fuels from four perspectives: (i) technology, (ii) infrastructure, (iii) scalability, and (iv) regulations. The obtained quantitative results indicate that the energy consumption to produce liquified natural gas, liquefied renewable methane, and liquefied green hydrogen is about 0.49, 31.4, and 62.3 kWhe/kg of fuel, respectively. The energy consumption to store liquified hydrogen in a 2,000 m3 on-land storage tank for one day while recovering 100% of the generated boil-off gas is about 4,840 kWh. Moreover, the qualitative results indicate that the infrastructure is ready, and regulations are available to use liquefied renewable methane as fuel, whereas the infrastructure of liquified hydrogen still needs to be ready, and the associated regulations require amendments. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.fuel.2023.128779